Early in vitro results indicate that de-O-acetylated sialic acids increase Selectin binding in cancers - Das, Kakali; Schulte, Megan; Gerhart, Megan; Bayoumi, Hala; Paulson, Delayna; Fink, Darci M.; Parrish, Colin; Willand-Charnley, Rachel (Frontiers in Oncology, 2024)
Cancers utilize a simple glycan, Sialic Acid, to engage in metastatic processes via the Sialic acid (Sia) -Selectin pathway. Selectins recognize and bind to sialylated substrates, resulting in adhesion, migration, and extravasation, however, how deviations from the canonical form of Sia regulate binding to Selectin receptors (E, L, and P) on hemopoietic cells resulting in these metastatic processes, remained a gap in knowledge. De-O-acetylated Sias has been recently shown to be an integral substrate to the binding of sialic acid binding proteins. The two proteins responsible for regulating the acetyl functional group on Sia’s C6 tail, are Sialic acid acetylesterase (SIAE) and Sialic acid O acetyltransferase (CASD1). To elucidate the contribution of functional group alterations on Sia, 9-O and 7,9-O-acetylation of Sia was modulated via the use of CRISRP-Cas9 gene editing and with Sialyl Glycan Recognition Probes, to produce either O-acetylated-Sia or de-O-acetylated- Sia, respectively. In vitro experiments revealed that increased cell surface expression of de-O-acetylated- Sia resulted in an increase in Selectin binding, enhanced cell proliferation, and increased migration capabilities both in lung and colon cancer. These results delineate for the first time the mechanistic contribution of de-O-acetylated-Sia to Selectin binding, reinforcing the importance of elucidating functional group alterations on Sia and their contribution. Without accurate identification of which functionalized form of Sia is being utilized to bind to sialic acid binding proteins, we cannot accurately produce glycan therapeutics with the correct specificity and reactivity, thus this work contributes an integral component in the development of promising therapeutic avenues, for example in the realm of enzyme antibody drug conjugates.